Preparation process of composite current collector, composite current collector and negative-electrode-free sodium metal battery
By using aromatic diamines, acrylate monomers and polyester polymers in an anode-free sodium metal battery, combined with graphene, the problems of uneven deposition of sodium ion insertion and sodium dendrites are solved. , improves the battery's cycle performance and Coulomb efficiency, and achieves the improvement of high energy density and safety performance.
Patent Information
- Application Number
- CN202411285523.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-09-13
AI Technical Summary
The uneven deposition of sodium ions in the negative electrode, resulting in rapid capacity decay and low Coulomb efficiency due to uneven sodium ions embedded, and the lack of negative electrode material constraints lead to sodium dendrites growth problems, affecting battery performance.
Aromatic diamine, acrylate monomer and polyester polymer are used to form a three-dimensional porous fluid gel through hydrothermal reaction, combined with graphene as a sheet skeleton, and composited on the current collector to form a composite liquid collector to control sodium Metal deposition and inhibition of sodium dendrites.
Effectively inhibit sodium dendrites, improve the battery circulation performance and Coulomb efficiency, extend the battery capacity development time, and improve the battery safety and high energy density.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of material preparation, and in particular to a preparation process of a composite current collector, a composite current collector and a negative electrode-free sodium metal battery. Background Art
[0002] As the application of lithium-ion battery technology in consumer electronics, electric vehicles, energy storage and other markets gradually expands, the problem of insufficient lithium resources has also begun to emerge. Sodium-based batteries have gradually attracted attention because the earth has a sufficiently high abundance of sodium elements, and they have an important strategic position in application fields with high cost requirements such as energy storage. The large-scale application of sodium-ion batteries is limited by problems such as low specific capacity of sodium-ion batteries.
[0003] The negative electrode-free sodium metal battery does not have any sodium ion embedding material on the negative electrode side, only the negative electrode current collector, which can work as the negative terminal of the sodium metal battery after the initial charging process, thereby providing a higher operating voltage and significantly improving the volume energy density and mass energy density due to the reduction in battery volume and weight.
[0004] However, there are currently two major problems with negative electrode-free sodium metal batteries: First, due to the limited amount of active sodium in the battery, the SEI film is constantly consuming sodium ions and breaking and rebuilding as the volume of the deposited metallic sodium changes, resulting in extremely rapid capacity decay; second, in the process of repeated embedding and extraction of sodium ions, without the constraints of negative electrode materials, sodium ions are prone to uneven deposition on the current collector, resulting in "dead sodium", which affects the capacity and coulombic efficiency of the negative electrode-free battery.
[0005] Therefore, compared with electrodes with negative electrode active materials, the negative electrode current collector of negative electrode-free sodium metal batteries has a more prominent sodium dendrite growth problem, and the battery has problems such as fast capacity decay and low coulombic efficiency. Therefore, a new negative electrode current collector or negative electrode-free sodium metal battery is urgently needed to meet the needs of high capacity and high safety performance negative electrode-free sodium metal batteries, while further improving sodium dendrites, cycle and coulombic efficiency. Summary of the invention
[0006] The object of the present invention is to provide a preparation process of a composite current collector, a composite current collector and a negative electrode-free sodium metal battery. The composite current collector can effectively inhibit sodium dendrites and improve the cycle performance and coulombic efficiency of the battery while maintaining the high capacity of the negative electrode-free sodium metal battery.
[0007] To achieve the above object, the present invention provides a process for preparing a composite current collector, comprising the steps of:
[0008] (1) mixing an aromatic diamine, an acrylate monomer and a polyester polymer, adding an initiator, and then adding a graphene solution to obtain a polymer solution;
[0009] (2) subjecting the polymer solution to a hydrothermal reaction to obtain a three-dimensional porous fluid gel;
[0010] (3) Compounding the three-dimensional porous fluid gel on a current collector to obtain a composite current collector.
[0011] In the preparation process of the present invention, aromatic diamine and acrylate monomers are polymerized under the action of an initiator and a hydrothermal reaction to obtain a polymer as a horizontal and vertical skeleton, a polyester polymer as an interlayer crosslinking agent, and graphene as a sheet skeleton, thereby compounding a three-dimensional porous fluid gel on the current collector. The three-dimensional porous structure of the three-dimensional porous fluid gel can control the deposition size of sodium metal on the current collector to suppress its uneven deposition morphology and avoid the generation of dead sodium. The graphene distributed in the three-dimensional porous structure has high mechanical properties, which can suppress the volume change of the deposited metallic sodium and avoid rupture during the cycle process. The three-dimensional porous fluid gel thus formed can improve the gram capacity and cycle performance of the negative electrode-free sodium metal battery. The preparation process of the composite current collector provided by the present invention is simple, highly feasible, and easy to realize industrial production.
[0012] As a technical solution of the present invention, the aromatic diamine includes at least one of o-phenylenediamine, m-phenylenediamine and p-phenylenediamine, the acrylate monomer includes at least one of methyl methacrylate, ethyl methacrylate, methyl acrylate and ethyl acrylate, and the polyester polymer includes polyethylene glycol diacrylate (PEGDA) and / or polypropylene glycol diacrylate (PPGDA).
[0013] As a technical solution of the present invention, the mass ratio of the aromatic diamine, the acrylic ester monomer and the polyester polymer is 1-5:1:4-10.
[0014] As a technical solution of the present invention, the sum of the masses of the aromatic diamine, the acrylate monomer and the polyester polymer is m, the mass of the initiator is n, n / m is 0.001 to 0.010, and the initiator includes at least one of azobisisobutyronitrile, azobisisoheptanenitrile and dimethyl azobisisobutyrate.
[0015] As a technical solution of the present invention, the sum of the masses of the aromatic diamine, the acrylate monomer and the polyester polymer is m, the mass of the graphene solution is p, p / m is 0.01 to 0.10, and the graphene solution is an aqueous solution with a graphene mass concentration of 3 to 10 mg / ml.
[0016] As a technical solution of the present invention, the temperature of the hydrothermal reaction is 70-100° C. and the time is 5-15 hours.
[0017] As a technical solution of the present invention, the porosity of the three-dimensional porous fluid gel is 40-75%, and the viscosity is 5000-15000 cp.s.
[0018] As a technical solution of the present invention, the composite comprises first extruding or coating on the current collector and then hot pressing, the hot pressing temperature is 250-450°C, the pressure is 100-300Mpa, and the hot pressing time is 5-30s.
[0019] The second aspect of the present invention provides a composite current collector prepared by the aforementioned composite current collector preparation process, comprising a copper foil and a gel layer composited on the copper foil, wherein the gel layer has a thickness of 1 to 10 μm.
[0020] A third aspect of the present invention provides a negative electrode-free sodium metal battery, comprising a composite current collector, a separator and a positive electrode sheet stacked in sequence, wherein the composite current collector is a composite current collector prepared by the aforementioned composite current collector preparation process or the aforementioned composite current collector. DETAILED DESCRIPTION
[0021] The composite current collector of the present invention can be applied to a sodium metal battery without negative electrode, and it can be applied to a wound sodium metal battery without negative electrode whose battery core is a wound type, and it can also be applied to a laminated sodium metal battery without negative electrode. The sodium metal battery without negative electrode comprises a composite current collector, a separator and a positive electrode sheet stacked in sequence, and the composite current collector, the separator and the positive electrode sheet are overlapped to obtain a laminated body. Multiple laminated bodies are stacked to obtain a battery core of a laminated sodium metal battery without negative electrode, and a single laminate is wound to obtain a battery core of a wound sodium metal battery without negative electrode. The battery core is sealed in a packaging bag and injected with liquid to obtain a sodium metal battery without negative electrode.
[0022] The positive electrode sheet can be a conventional all-solid-state battery sheet. The positive electrode active material, positive electrode conductive agent and positive electrode binder are mixed to form a positive electrode slurry, which is then coated on aluminum foil, dried and rolled to obtain a positive electrode sheet. The positive electrode active materials include α-NaFeO2, NaCoO2, Na 0.7 [Fe 0.7 Mn 0.3 ]O2、Na(Mn 0.25 Fe 0.25 Co 0.25 Ni 0.25 )O2, NaMnO2, Na 0.5 [Fe 1 / 2 Mn 1 / 2 ]O2、Na 0.67 [Fe 1 / 2 Mn 1 / 2 ]O2, Na[Ni 0.35 Fe 0.40 Mn 0.25 ]O2, Na[Ni0.30 Fe 0.45 Mn 0.25 ]O2, Na[Ni 0.25 Fe 0.50 Mn 0.25 ]O2, Na[Ni 0.20 Fe 0.55 Mn 0.25 ]O2、Na 0.67 [Mn 0.60 Ni 0.15 Fe 0.25 ]O2、Na[Li 0.05 (Ni 0.25 Fe 0.25 Mn 0.5 ) 0.95 ]O2, Na2FePO4F, Na4Fe2(CN)6, NaNi 0.33 Fe 0.33 Mn 0.33 At least one of O2, NaFePO4, Na2FeP2O7, Na2MnPO4F, NaCoPO4, Na3V2(PO4)3, NaCrO2 and Na2Fe2(SO4)3. The positive electrode active material includes not only the above materials but also the corresponding coating and doping materials. The positive electrode conductive agent includes at least one of conductive carbon black, conductive graphite, carbon fiber, carbon nanotubes and graphene. The positive electrode binder includes polyvinylidene fluoride. The positive electrode slurry is prepared by using NMP as an organic solvent. The mass ratio of the positive electrode active material, the positive electrode conductive agent and the positive electrode binder can be 90-98:1-5:1-5.
[0023] The separator is not particularly limited and may be made of polypropylene, polyethylene, paper, glass fiber, fiber resin, non-woven fabric, and the like.
[0024] The injected electrolyte includes sodium salt and non-aqueous organic solvent. The sodium salt includes at least one of sodium hexafluorophosphate, sodium difluorooxalatoborate, sodium tetrafluoroborate, sodium bisoxalatoborate, sodium perchlorate, sodium hexafluoroarsenate, sodium bis(fluorosulfonyl)imide, sodium trifluoromethylsulfonate and sodium bis(trifluoromethylsulfonyl)imide. The non-aqueous organic solvent is selected from at least one of carbonate organic solvents, carboxylate organic solvents and ether organic solvents. Specifically, the non-aqueous organic solvent may be, but is not limited to, at least one of ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), pentylene carbonate, vinylene carbonate (VC), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), propylene carbonate (PC), butyl acetate (n-Ba), propyl propionate (n-PP), ethyl propionate (EP), ethyl butyrate (Eb), ethylene glycol dimethyl ether (DME), ethylene glycol diethyl ether (ECS), diethylene glycol dimethyl ether (DEGME), triethylene glycol dimethyl ether (TEGDME), tetraethylene glycol dimethyl ether (TEGDME), 1,3-dioxolane (DOL), tetrahydrofuran (THF), methyltetrahydrofuran (MTHF), diphenyl ether and crown ether (CE).
[0025] The composite current collector includes a copper foil and a gel layer composited on the copper foil, and the thickness of the gel layer is 1 to 10 μm. As an example, the thickness can be, but not limited to, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, and 10 μm. The thinner the gel layer, the smaller the volume and weight of the battery, thereby increasing the volume energy density and mass energy density of the battery.
[0026] The preparation process of the composite current collector includes the following steps.
[0027] (1) Aromatic diamine, acrylate monomer and polyester polymer are mixed, an initiator is added, and then a graphene solution is added to obtain a polymer solution.
[0028] (2) The polymer solution is subjected to a hydrothermal reaction to obtain a three-dimensional porous fluid gel.
[0029] (3) The three-dimensional porous fluid gel is composited onto a current collector to obtain a composite current collector.
[0030] Wherein, the aromatic diamine in step (1) includes at least one of o-phenylenediamine, m-phenylenediamine and p-phenylenediamine. The acrylate monomer includes at least one of methyl methacrylate, ethyl methacrylate, methyl acrylate and ethyl acrylate. The polyester polymer includes polyethylene glycol diacrylate (PEGDA) and / or polypropylene glycol diacrylate (PPGDA). The mass ratio of the aromatic diamine, the acrylate monomer and the polyester polymer is 1 to 5:1:4 to 10. As an example, the mass ratio of the three can be but is not limited to 1:1:4, 1:1:7, 1:1:10, 3:1:4, 3:1:7, 3:1:10, 5:1:4, 5:1:7, 5:1:10. The sum of the masses of the aromatic diamine, the acrylate monomer and the polyester polymer is m, the mass of the initiator is n, n / m is 0.001 to 0.010, and as an example, n / m can be, but not limited to, 0.001, 0.002, 0.003, 0.004, 0.005, 0.006, 0.007, 0.008, 0.009, 0.010. The initiator includes at least one of azobisisobutyronitrile, azobisisoheptanenitrile and dimethyl azobisisobutyrate. The mass of the graphene solution is p, p / m is 0.01 to 0.10, and as an example, p / m can be, but not limited to, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10. The graphene solution is an aqueous solution with a graphene mass concentration of 3 to 10 mg / ml. For example, the concentration can be, but is not limited to, 3 mg / ml, 4 mg / ml, 5 mg / ml, 6 mg / ml, 7 mg / ml, 8 mg / ml, 9 mg / ml, and 10 mg / ml. By controlling the ratio of the raw materials and regulating the degree of polymerization, the three-dimensional porous fluid gel prepared can have a certain porosity and viscosity, so as to facilitate the subsequent processing and use of the gel, and maintain a certain porosity to control the deposition size of the sodium metal on the current collector, so as to suppress its uneven deposition morphology and avoid the generation of dead sodium.
[0031] In step (2), the temperature of the hydrothermal reaction is 70 to 100°C. As an example, the temperature can be, but not limited to, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, and 100°C. The time of the hydrothermal reaction is 5 to 15 hours. As an example, the time can be, but not limited to, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, and 15 hours. Under hydrothermal conditions, the aromatic diamine and the acrylate monomer undergo polymerization. The porosity of the three-dimensional porous fluid gel is 40 to 75%. As an example, the porosity can be, but not limited to, 40%, 45%, 50%, 55%, 60%, 65%, 70%, and 75%. The viscosity is 5000-15000cp.s. As an example, the viscosity can be but is not limited to 5000cp.s, 6000cp.s, 7000cp.s, 8000cp.s, 9000cp.s, 10000cp.s, 11000cp.s, 12000cp.s, 13000cp.s, 14000cp.s, and 15000cp.s. The three-dimensional porous fluid gel has a low viscosity and a certain fluidity, so it is convenient for subsequent compounding on the current collector.
[0032] In step (3), the compounding includes first extruding or coating the three-dimensional porous fluid gel on the current collector and then hot pressing, the hot pressing temperature is 250-450°C, as an example, the hot pressing temperature can be but not limited to 250°C, 280°C, 300°C, 320°C, 340°C, 360°C, 380°C, 400°C, 420°C, 440°C, 450°C. The pressure is 100-300Mpa, as an example, the pressure can be but not limited to 100Mpa, 120Mpa, 150Mpa, 180Mpa, 200Mpa, 230Mpa, 250Mpa, 270Mpa, 300Mpa. The hot pressing time is 5-30s, as an example, the time can be but not limited to 5s, 10s, 15s, 20s, 25s, 30s. The current collector may be a copper foil, and the three-dimensional porous fluid gel may be extruded or coated on one side or both sides of the current collector.
[0033] In order to better illustrate the purpose, technical scheme and beneficial effects of the present invention, the present invention will be further described below in conjunction with specific embodiments. It should be noted that the following implementation method is a further explanation of the present invention and should not be used as a limitation of the present invention.
[0034] Example 1
[0035] This embodiment is a composite current collector, which includes a copper foil and a gel layer composited on the copper foil, wherein the thickness of the gel layer is 7 μm.
[0036] The preparation process of the composite current collector includes the following steps:
[0037] (1) o-phenylenediamine, methyl methacrylate and polyethylene glycol diacrylate are mixed in a mass ratio of 2:1:5 to obtain a first mixture, 0.5 wt.% of azobisisobutyronitrile is added to the first mixture and mixed evenly, and then 6 wt.% of a graphene solution (aqueous solution with a graphene concentration of 6 mg / ml) is added to the first mixture and mixed evenly to obtain a polymer solution;
[0038] (2) subjecting the polymer solution to a hydrothermal reaction at 90° C. for 8 h to obtain a three-dimensional porous fluid gel having a porosity of 77% and a viscosity of 7000 cp.s;
[0039] (3) The three-dimensional porous fluid gel is extruded onto the surface of a copper foil and then hot-pressed at 300°C and 150 MPa for 20 seconds to obtain a composite current collector.
[0040] Example 2
[0041] This embodiment is a composite current collector, which includes a copper foil and a gel layer composited on the copper foil, wherein the thickness of the gel layer is 8 μm.
[0042] The preparation process of the composite current collector includes the following steps:
[0043] (1) o-phenylenediamine, methyl methacrylate and polyethylene glycol diacrylate are mixed in a mass ratio of 5:1:9 to obtain a first mixture, 1.0 wt.% of azobisisobutyronitrile is added to the first mixture and mixed evenly, and then 10.0 wt.% of a graphene solution (aqueous solution with a graphene concentration of 9 mg / ml) is added to the first mixture and mixed evenly to obtain a polymer solution;
[0044] (2) subjecting the polymer solution to a hydrothermal reaction at 90° C. for 8 h to obtain a three-dimensional porous fluid gel having a porosity of 60% and a viscosity of 8000 cp.s;
[0045] (3) The three-dimensional porous fluid gel is extruded onto the surface of a copper foil and then hot-pressed at 300°C and 150 MPa for 20 seconds to obtain a composite current collector.
[0046] Example 3
[0047] This embodiment is a composite current collector, which includes a copper foil and a gel layer composited on the copper foil, wherein the thickness of the gel layer is 7 μm.
[0048] The preparation process of the composite current collector includes the following steps:
[0049] (1) o-phenylenediamine, methyl methacrylate and polyethylene glycol diacrylate are mixed in a mass ratio of 1:1:7 to obtain a first mixture, 0.3 wt.% of azobisisobutyronitrile is added to the first mixture and mixed evenly, and then 3 wt.% of a graphene solution (aqueous solution with a graphene concentration of 4 mg / ml) is added to the first mixture and mixed evenly to obtain a polymer solution;
[0050] (2) subjecting the polymer solution to a hydrothermal reaction at 90° C. for 8 h to obtain a three-dimensional porous fluid gel having a porosity of 65% and a viscosity of 5500 cp.s;
[0051] (3) The three-dimensional porous fluid gel is extruded onto the surface of a copper foil and then hot-pressed at 300°C and 150 MPa for 20 seconds to obtain a composite current collector.
[0052] Example 4
[0053] This embodiment is a composite current collector, which includes a copper foil and a gel layer composited on the copper foil, wherein the thickness of the gel layer is 10 μm.
[0054] The preparation process of the composite current collector includes the following steps:
[0055] (1) p-phenylenediamine, methyl acrylate and polypropylene glycol diacrylate are mixed in a mass ratio of 2:1:5 to obtain a first mixture, 0.5 wt.% of azobisisoheptanenitrile is added to the first mixture and mixed evenly, and then 6 wt.% of a graphene solution (aqueous solution with a graphene concentration of 6 mg / ml) is added to the first mixture and mixed evenly to obtain a polymer solution;
[0056] (2) subjecting the polymer solution to a hydrothermal reaction at 90° C. for 8 h to obtain a three-dimensional porous fluid gel having a porosity of 73% and a viscosity of 7500 cp.s;
[0057] (3) The three-dimensional porous fluid gel is extruded onto the surface of a copper foil and then hot-pressed at 300°C and 150 MPa for 20 seconds to obtain a composite current collector.
[0058] Example 5
[0059] This embodiment is a composite current collector, which includes a copper foil and a gel layer composited on the copper foil, wherein the thickness of the gel layer is 9 μm.
[0060] The preparation process of the composite current collector includes the following steps:
[0061] (1) o-phenylenediamine, methyl methacrylate and polyethylene glycol diacrylate are mixed in a mass ratio of 2:1:5 to obtain a first mixture, 0.5 wt.% of azobisisobutyronitrile is added to the first mixture and mixed evenly, and then 6 wt.% of a graphene solution (aqueous solution with a graphene concentration of 6 mg / ml) is added to the first mixture and mixed evenly to obtain a polymer solution;
[0062] (2) subjecting the polymer solution to a hydrothermal reaction at 100° C. for 6 h to obtain a three-dimensional porous fluid gel having a porosity of 70% and a viscosity of 6000 cp.s;
[0063] (3) The three-dimensional porous fluid gel is extruded onto the surface of a copper foil and then hot-pressed at 400°C and 200 MPa for 10 seconds to obtain a composite current collector.
[0064] Comparative Example 1
[0065] This comparative example is a composite current collector, which includes a copper foil and a gel layer composited on the copper foil, wherein the thickness of the gel layer is 9 μm.
[0066] The preparation process of the composite current collector includes the following steps:
[0067] (1) mixing o-phenylenediamine, methyl methacrylate and polyethylene glycol diacrylate in a mass ratio of 2:1:5 to obtain a first mixture, adding 0.5 wt.% of azobisisobutyronitrile to the first mixture and mixing well to obtain a polymer solution;
[0068] (2) subjecting the polymer solution to a hydrothermal reaction at 90° C. for 8 h to obtain a three-dimensional porous fluid gel, wherein the porosity of the three-dimensional porous fluid gel is 45% and the viscosity is 10,000 cp.s;
[0069] (3) The three-dimensional porous fluid gel is extruded onto the surface of a copper foil and then hot-pressed at 300°C and 150 MPa for 20 seconds to obtain a composite current collector.
[0070] Comparative Example 2
[0071] This comparative example is a composite current collector. The composite current collector includes a copper foil and a gel layer composited on the copper foil, and the thickness of the gel layer is 11 μm. The preparation process of the composite current collector includes the following steps:
[0072] (1) o-phenylenediamine and methyl methacrylate are mixed in a mass ratio of 2:1 to obtain a first mixture, 0.5 wt.% of azobisisobutyronitrile is added to the first mixture and mixed evenly, and then 6 wt.% of a graphene solution (aqueous solution with a graphene concentration of 6 mg / ml) is added to the first mixture and mixed evenly to obtain a polymer solution;
[0073] (2) subjecting the polymer solution to a hydrothermal reaction at 90° C. for 8 h to obtain a three-dimensional porous fluid gel having a porosity of 40% and a viscosity of 9200 cp.s;
[0074] (3) The three-dimensional porous fluid gel is extruded onto the surface of a copper foil and then hot-pressed at 300°C and 150 MPa for 20 seconds to obtain a composite current collector.
[0075] The composite current collectors of Examples 1 to 5 and Comparative Examples 1 to 2 were assembled into a negative electrode-free sodium metal battery, and the assembly process was as follows. The prepared negative electrode-free sodium metal battery was subjected to an electrochemical performance test, and the test conditions were as follows. The test results are shown in Table 1.
[0076] (I) Preparation of negative electrode-free sodium metal battery
[0077] The composite current collectors of Examples 1 to 5 and Comparative Examples 1 to 2 were cut into samples as negative electrode current collectors by a cutting machine, with the gel layer facing the positive electrode direction, and a sodium vanadium phosphate positive electrode sheet (sodium vanadium phosphate loading of 16 mg cm 2 ) was used as the counter electrode to assemble the full battery, 1M NaFP6 / diethylene glycol dimethyl ether (DEGDME) was used as the electrolyte, and a porous single-layer polypropylene membrane was used as the separator. A negative electrode-free sodium metal battery was assembled in a glove box (high-purity argon atmosphere, in which the oxygen and water contents were both less than 0.1ppm).
[0078] (II) Electrochemical performance test
[0079] 1. First Coulombic efficiency test
[0080] The negative electrode-free sodium metal battery is subjected to aging, formation, sealing, and capacity division steps according to conventional means, wherein the charging capacity during the formation process is recorded as C1, the charging capacity during the capacity division process is recorded as C2, and the discharge capacity during the capacity division process is recorded as C0.
[0081] First coulomb efficiency = C0 / (C1+C2)×100%
[0082] 2. Normal temperature cycle performance test
[0083] A negative electrode-free sodium metal battery was placed in an environment of 25°C, charged at a constant current of 1C to 4.0V, then charged at a constant voltage to a current of 0.05C, and then discharged at a constant current of 1C to 2.0V. This cycle was repeated for 500 cycles, and the discharge capacity of the first cycle and the last cycle were recorded. The capacity retention rate of the room temperature cycle was calculated according to the following formula.
[0084] Capacity retention rate = discharge capacity of the last cycle / discharge capacity of the first cycle × 100%
[0085] Table 1 Electrochemical performance test results of Examples 1 to 5 and Comparative Examples 1 to 2
[0086] Example First coulombic efficiency / % Capacity retention rate after 500 cycles / % Example 1 88.6 90.2 Example 2 88.0 89.9 Example 3 89.0 90.8 Example 4 88.5 90.1 Example 5 88.3 90.3 Comparative Example 1 82.5 75.5 Comparative Example 2 81.8 76.0
[0087] From the results in Table 1, it can be seen that a three-dimensional porous fluid gel can be obtained by using a polymer obtained by polymerization of aromatic diamine and acrylate monomers as a horizontal and vertical skeleton, a polyester polymer as an interlayer crosslinker, and graphene as a sheet skeleton. The three-dimensional porous fluid gel is compounded on a current collector to prepare a negative electrode-free sodium metal battery with high coulombic efficiency and better cycle performance. This may be because the three-dimensional porous structure of the three-dimensional porous fluid gel can control the deposition size of sodium metal on the current collector to inhibit its uneven deposition morphology and avoid the generation of dead sodium. Graphene distributed in the three-dimensional porous structure has high mechanical properties, which can inhibit the volume change of the deposited metal sodium and avoid rupture during the cycle process. Therefore, the specific capacity and cycle performance of the negative electrode-free sodium metal battery can be improved.
[0088] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention is described in detail with reference to the preferred embodiments, it is not limited to those listed in the embodiments. Those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A process for preparing a composite current collector, characterized in that: Includes steps: (1) mixing an aromatic diamine, an acrylate monomer and a polyester polymer, adding an initiator, and then adding a graphene solution to obtain a polymer solution; (2) subjecting the polymer solution to a hydrothermal reaction to obtain a three-dimensional porous fluid gel; (3) Compounding the three-dimensional porous fluid gel on a current collector to obtain a composite current collector.
2. The preparation process of the composite current collector according to claim 1, characterized in that: The aromatic diamine includes at least one of o-phenylenediamine, m-phenylenediamine and p-phenylenediamine, the acrylate monomer includes at least one of methyl methacrylate, ethyl methacrylate, methyl acrylate and ethyl acrylate, and the polyester polymer includes polyethylene glycol diacrylate and / or polypropylene glycol diacrylate.
3. The preparation process of the composite current collector according to claim 1, characterized in that: The mass ratio of the aromatic diamine, the acrylic ester monomer and the polyester polymer is 1-5:1:4-10.
4. The preparation process of the composite current collector according to claim 1, characterized in that: The sum of the masses of the aromatic diamine, the acrylic ester monomer and the polyester polymer is m, the mass of the initiator is n, n / m is 0.001-0.010, and the initiator includes at least one of azobisisobutyronitrile, azobisisoheptanenitrile and dimethyl azobisisobutyrate.
5. The process for preparing the composite current collector according to claim 1, characterized in that: The sum of the masses of the aromatic diamine, the acrylate monomer and the polyester polymer is m, the mass of the graphene solution is p, p / m is 0.01-0.10, and the graphene solution is an aqueous solution with a graphene mass concentration of 3-10 mg / ml.
6. The process for preparing the composite current collector according to claim 1, characterized in that: The temperature of the hydrothermal reaction is 70-100° C. and the time is 5-15 hours.
7. The process for preparing the composite current collector according to claim 1, characterized in that: The porosity of the three-dimensional porous fluid gel is 40-75%, and the viscosity is 5000-15000 cp.s.
8. The process for preparing the composite current collector according to claim 1, characterized in that: The composite comprises extruding or coating on the current collector first and then hot pressing, the hot pressing temperature is 250-450° C., the pressure is 100-300 MPa, and the hot pressing time is 5-30 seconds.
9. The composite current collector prepared by the process for preparing a composite current collector according to any one of claims 1 to 8, characterized in that: The invention comprises a copper foil and a gel layer compounded on the copper foil, wherein the thickness of the gel layer is 1 to 10 μm.
10. A negative electrode-free sodium metal battery, characterized in that: The invention comprises a composite current collector, a separator and a positive electrode sheet which are stacked in sequence, wherein the composite current collector is a composite current collector prepared by the composite current collector preparation process described in any one of claims 1 to 8 or a composite current collector described in claim 9.
Citation Information
Patent Citations
Graphene-like composite cathode current collector and preparation method thereof, and application of graphene-like composite cathode current collector
CN110364738A
Energy storage devices and systems
CN110574205A
Solid polymer electrolyte, preparation method thereof and application of solid polymer electrolyte in secondary battery
CN117673461A
Modified current collector, preparation method thereof and non-cathode sodium battery
CN117747848A
Graphene compound and manufacturing method thereof, electrolyte, and power storage device
US20180108944A1
Cited By
Negative-electrode-free sodium-ion battery current collector based on dynamic self-adaptive interface layer and preparation method of negative-electrode-free sodium-ion battery current collector
CN121839534A
A negative electrode-free sodium-ion battery current collector based on a dynamic adaptive interface layer and a preparation method thereof
CN121839534B